2015
DOI: 10.1007/s00784-015-1675-1
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the dentoalveolar effects of slow and rapid maxillary expansion in complete bilateral cleft lip and palate patients: a randomized clinical trial

Abstract: Both expansion procedures can be similarly indicated to correct maxillary arch constriction in patients with BCLP in the mixed dentition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(40 citation statements)
references
References 49 publications
1
25
2
Order By: Relevance
“…These results are comparable to those obtained with other devices that determine a slow expansion with evidence of separation of the median palatine suture radiologically detected in cases from 50% to 80% [21,22,23].…”
Section: Introductionsupporting
confidence: 87%
“…These results are comparable to those obtained with other devices that determine a slow expansion with evidence of separation of the median palatine suture radiologically detected in cases from 50% to 80% [21,22,23].…”
Section: Introductionsupporting
confidence: 87%
“…Both expansion modalities were capable of correcting the posterior crossbites in patients with complete bilateral cleft lip and palate. Some clinical important differences, however, were observed in this study and reported in the literature (Medeiros Alves et al, 2015), as the inconvenience of a greater expansion therapy time and a less practical clinical procedure to orthodontist once it is necessary to take the appliance out for activations with quad-helix appliance. On the other hand, slow maxillary expansion permits to achieve differential expansion with a greater increase of the inter canines distance than the increase of intermolars distance .…”
Section: Final Considerationscontrasting
confidence: 60%
“…No differences were observed for RME and SME except the capability of quad-helix in promoting differential expansions in the anterior and posterior regions. A shorter therapy time was observed for RME (Medeiros Alves et al, 2015).…”
Section: Introductionmentioning
confidence: 87%
“…This study was approved by the Ethics Committee of Bauru Dental School, University of São Paulo, Brazil. Sample size was calculated based on an alpha level of significance of 5% and a test power of 80%, to detect a mean difference of 1.23 degrees, with a standard deviation of 2.01 degrees for molar and premolar inclinations . Thus, 22 subjects in each group were necessary.…”
Section: Methodsmentioning
confidence: 99%
“…Sample size was calculated based on an alpha level of significance of 5% and a test power of 80%, to detect a mean difference of 1.23 degrees, with a standard deviation of 2.01 degrees for molar and premolar inclinations. 5 The archwire sequence used was as follows: (a) 0.014, (b) 0.016 and (c) 0.018-inch conventional NiTi archwires, which were maintained until correction of any crowding and rotations, (d) 0.016, (e) 0.018, (f) 0.020, and, finally, (g) 0.019 × 0.025-inch rectangular stainless steel (SS) archwires. Interlandi's diagram was used to customize the dental arch form of each patient.…”
Section: Materials and Me Thodsmentioning
confidence: 99%